2019
DOI: 10.21203/rs.2.10600/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Etiological Agents for Chronic Suppurative Otitis Media in a Tertiary Hospital in Tanzania.

Abstract: Objective: Chronic suppurative otitis media is among the most common otological condition reported in otorhinolaryngology practice commonly attributing to preventable hearing loss. The aim of this study was to determine the prevalence and etiological agents for chronic suppurative otitis media in our department. Results: A total of 5591 patients were recruited in this study and only 79 (1.4%) had chronic suppurative otitis media. A male preponderance 43 (54.4%) was noted in this study and the left ear (58.2%) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…10 In present study we found a slight male preponderance, this can be attributed to the fact that male patients have been exposed to more of pollution like dust, pollen, taking bath in the pond in rural setup. These results are similar to study conducted by Abraham et al 11,12 In current study, majority were from a rural setup than urban setup. This was similar to study conducted by Bandyopadhyay et al 13 Also our hospital is visited by majority of the rural patients for their health care needs.…”
Section: Discussionsupporting
confidence: 92%
“…10 In present study we found a slight male preponderance, this can be attributed to the fact that male patients have been exposed to more of pollution like dust, pollen, taking bath in the pond in rural setup. These results are similar to study conducted by Abraham et al 11,12 In current study, majority were from a rural setup than urban setup. This was similar to study conducted by Bandyopadhyay et al 13 Also our hospital is visited by majority of the rural patients for their health care needs.…”
Section: Discussionsupporting
confidence: 92%
“…This study used subject selection with total sampling, the dominance of male sex may be a coincidence finding, there are no known anatomical or genetic differences between men and women associated with ear infections, especially CSOM. 2,6 The success of treating bacterial infections is the result of working between antibiotics and the immune system. Antibiotic resistance and the immune system are related to infection, the adaptation of bacteria to the immune system affects the spectrum of antibiotic resistance so that bacteria can become more resistant.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was like the study by Abraham et al, 67.2% were metastatic lymph nodes, and the primary cancers occurs commonly from the nasopharynx (21.31%) and oropharynx (21.31%). 20 Benign neck lumps are less common in adults. 2,6 However, benign tumours arising from the thyroid and salivary glands, are relatively commonly seen in adults.…”
Section: Discussionmentioning
confidence: 99%